Implementing Smart Working in Public Administration: a follow up study - Di Tecco, Cristina; Ronchetti, Matteo; Russo, Simone; Ghelli, Monica; Rondinone, Bruna Maria; Persechino, Benedetta; Iavicoli, Sergio (La Medicina del Lavoro, 2021)
Background: Starting from February 2020, in Italy most organizations have had a forced transition to flexible working practice - called “smart working in emergency” – due to the Covid-19 epidemic outbreak. This allowed to continue work activities and services and contributed to contain the risk of infection in different sectors, particularly in the public administration. Objectives: This follow up study focussed on a panel of 187 workers from the Italian Workers’ Compensation Authority taking part to a pilot project “Smart Working in INAIL” from January 2019 to December 2019. The aim was to investigate the effects of work organization on work attitudes, work-life balance and health outcomes before and after the introduction of the smart working. Methods: The data were collected at two time points through a web-based questionnaire. The first wave aimed to collect information up to one month before the implementation of the smart working. The second wave aimed to collect information about potential changes occurred after one year of smart working. Results: This study showed that high demands, low control and low social support might lead to reduced well-being and less satisfaction with work, and have an effect on work engagement and work-life balance. Particularly, improving social support can moderate the negative impact of high strain on well-being, preventing work-life imbalance and risk of isolation. Discussion: Findings and future perspectives are discussed to support stakeholders in defining policies and practices concerning health and wellbeing at work while preserving productivity, for a successful implementation of smart working in the public administration.